IMPLEMENTASI PERMENPAN RB NOMOR 33 TAHUN 2011 TENTANG PEDOMAN ANALISIS JABATAN DI SEKRETARIAT DAERAH KABUPETEN OGAN KOMERING ULU (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2023)
The purpose of this research is to find out the Implementation of Permenpan RB No.33 Year 2011 on Guidelines for Position Analysis in oku District Secretariat. This type of research is quantitative research with the research approach is descriptive. The population of this research is all State Civil Apparatus (ASN) in the Secretariat of OKU Regency which amounts to 176 people. The sample of this study amounted to 44 ASN people taken 25% of the population. Data collection techniques are questionnaires and data collection tools in the form of questionnaires. Data analysis techniques use descriptive percentative techniques. Based on the results of research and discussion, Implementation permenpan RB No.33 Year 2011 on Guidelines for Analysis of Study Positions in the Oku District Secretariat for the indicators of The Preparation Stage of Position Analysis obtained from 2 items, an average percentage of 94.32% with an excellent category. In the Field Implementation Stage Indicators Position Analysis data obtained from 9 items obtained an average percentage of 84.08% with good categories. Position Analysis Stage Indicator based on data obtained from 3 items obtained an average percentage of 74.06% with sufficient categories. From the results of the study, it can be concluded that the Implementation of Permenpan RB No.33 Year 2011 on Guidelines for Position Analysis in oku District Secretariat has been carried out properly.